The Concept of Justice in Buddhism: A Case Study of Caá¹‡á¸Äla in JÄtakaá¹á¹hakathÄ - Ratchatakorntrakoon, Ratchaneekorn; Chongstitvatana, Suchitra (International Journal of Engineering and Technology, 2018)
This article aims to study the function of Caá¹‡á¸Äla, the outer caste character in JÄtakaá¹á¹hakathÄ, the stories of the prior lives of the Buddha, and to study the relationship between the Caá¹‡á¸Äla characters and the concept of justice in these JÄtaka stories. In order to construct the concept of justice in Buddhism, and the framework of this study, Rawlsâ€™ theory regarding justice as fairness is used as a guideline for exploration of the Sutta, the Buddhist canon. The study reveals that the Caá¹‡á¸Äla characters appear in nine JÄtakas, playing significant roles in parts of many the prose narratives and the connection part of the story in order to illustrate that a low caste person can attain enlightenment. Three concepts of Dharma are conveyed by the Caá¹‡á¸Äla characters in JÄtakaá¹á¹hakathÄ: firstly, defilement causes humans in every caste to have suffering; secondly, every occurrence in oneâ€™s life depends on karma; and thirdly, humans in every caste have the potential to accomplish wisdom by understanding the path to eradicate suffering.Â Â Â Â